The role of altered protein acetylation in neurodegenerative disease - Kabir, Fariha; Atkinson, Rachel; Cook, Anthony L.; Phipps, Andrew James; King, Anna Elizabeth (Frontiers in Aging Neuroscience, 2023)
Acetylation is a key post-translational modification (PTM) involved in the regulation of both histone and non-histone proteins. It controls cellular processes such as DNA transcription, RNA modifications, proteostasis, aging, autophagy, regulation of cytoskeletal structures, and metabolism. Acetylation is essential to maintain neuronal plasticity and therefore essential for memory and learning. Homeostasis of acetylation is maintained through the activities of histone acetyltransferases (HAT) and histone deacetylase (HDAC) enzymes, with alterations to these tightly regulated processes reported in several neurodegenerative diseases including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD) and amyotrophic lateral sclerosis (ALS). Both hyperacetylation and hypoacetylation can impair neuronal physiological homeostasis and increase the accumulation of pathophysiological proteins such as tau, α-synuclein, and Huntingtin protein implicated in AD, PD, and HD respectively. Additionally, dysregulation of acetylation is linked to impaired axonal transport, a key pathological mechanism in ALS. This review article will discuss the physiological roles of protein acetylation and examine the current literature that describes altered protein acetylation in neurodegenerative disorders.